2015
DOI: 10.1016/j.idairyj.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Tensile testing to quantitate the anisotropy and strain hardening of mozzarella cheese

Abstract: a b s t r a c tWe explored anisotropy of mozzarella cheese: its presence is debated in the literature. Tensile testing proved a good method because the location and mode of failure were clear. Mozzarella cheese cut direct from the block showed no significant anisotropy, though confocal microscopy showed good structure alignment at a microscale. Deliberately elongated mozzarella cheese showed strong anisotropy with tensile strength in the elongation or fibre direction~3.5Â that perpendicular to the fibres. Temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…In tensile test on Mozzarella cheese, Ak & Gunasekaran (1997) found differences between mechanical results according to axis direction, while Bast et al (2015) did not found. Such author suggests that the isotropic behavior in tensile test with Mozzarella cheese may be found due to changes in cheese structure during the molding process.…”
Section: Effect Of Compression Directionmentioning
confidence: 79%
See 1 more Smart Citation
“…In tensile test on Mozzarella cheese, Ak & Gunasekaran (1997) found differences between mechanical results according to axis direction, while Bast et al (2015) did not found. Such author suggests that the isotropic behavior in tensile test with Mozzarella cheese may be found due to changes in cheese structure during the molding process.…”
Section: Effect Of Compression Directionmentioning
confidence: 79%
“…Disruption may also occur in the direction perpendicular to the fibers where a weak interaction between protein and fat exists (Taneya, Izutsu, Kimura, & Shioya, ), resulting in a low mechanical resistance. In tensile test on Mozzarella cheese, Ak & Gunasekaran () found differences between mechanical results according to axis direction, while Bast et al () did not found. Such author suggests that the isotropic behavior in tensile test with Mozzarella cheese may be found due to changes in cheese structure during the molding process.…”
Section: Resultsmentioning
confidence: 95%
“…5C showed strain hardening in the parallel direction but not in the perpendicular direction in all materials. A similar behaviour was reported byBast et al (2015) for mozzarella cheese andGrabowska et al (2014) for an anisotropic soy-gluten structure.…”
supporting
confidence: 86%
“…In the perpendicular direction, the fibres are just pulled apart. Here, the air bubbles work as a weak phase, similar to the role of the fat droplets in mozzarella cheese (Bast et al, 2015), which results in lower fracture strain and no strain hardening.…”
Section: Mechanical Propertiesmentioning
confidence: 91%
“…The few studies at processing temperatures (55–65C) highlight the complexity of the stretching process and that strain‐hardening is an important factor to consider during pasta‐filata cheese production (Ak and Gunasekaran ; Bast et al . ). We hypothesize that the relaxation behavior during production is a further crucial factor, which needs to be considered, because similar elongation parameters and different degrees of relaxation results in a different microstructure.…”
Section: Introductionmentioning
confidence: 97%